Effect of Carboxymethyl Cellulose and Alginate Coating Combined with Brewer Yeast on Postharvest Grape Preservation. (10th June 2013) - Yinzhe, Ren; Shaoying, Zhang
Abstract : The effect of carboxymethyl cellulose and alginate coating combined with brewer yeast on postharvest grape preservation was investigated. The postharvest grapes were coated with 2% of alginate and 3% of carboxymethyl cellulose combined with 1.5 × 10 9 CFU/mL of brewer yeast. The combined treatment samples showed good sensory character on day 13 compared with control samples or only coated samples. The increase of weight loss and decrease of total soluble solids of combined treatment grapes were restrained. Furthermore, the protective enzymes including superoxide dismutase, peroxidase, and catalase of combined treatment sample showed higher activities. Accordingly, the increase of malonaldehyde content was also restrained and more vitamin C was preserved in combined treatment samples. At day 13, the weight loss rate and the total soluble solids of grape treated with coating + yeast were 23.6% lower and 20.6% higher than those of control samples, respectively. Coating grapes with 2% of alginate and 3% of carboxymethyl cellulose combined with brewer yeast of 1.5 × 10 9 CFU/mL was a well-proven method to preserve postharvest grapes.